Extensive standing genetic variation from a small number of founders enables rapid adaptation in Daphnia - Anurag Chaturvedi (Nature Portfolio, 2021)
Standing genetic variation allows natural populations to evolve rapidly. Genome sequences of a resurrected Daphnia population show that genetic variation carried by only five founding individuals from the regional genotype pool is enough to fuel rapid evolution in response to strong selection pressures with no evidence of genetic erosion.